(untitled) (Hanoi, 2004)
The purpose of this book is to: Understand why social safeguards are important; present best practice guidance on the application of social safeguards of Vietnam and World Bank in project cycle ; present and explain the social safeguard requirements of the GOV and the WB; and advise on sources of further reading and information. This book covers best practice in implementation of social safeguards applied to the development of projects, including the importance of public consultation and disclosure therein. Environmental safeguards are covered in separate book prepared under this project. These guidelines are structured into three parts as follows: Part 1- Overviews of project cycles and Safeguards Policies of the world bank and Vietnam ; Part 2- Implementation of the World Bank safeguard on involuntary resettlement ; and Part 3- Implementation of safeguard policy on indigenous peoples
Keywords: Environmental policy,Environmental protection